1969
DOI: 10.1017/s0022112069000759
|View full text |Cite
|
Sign up to set email alerts
|

The deformation of a drop in a general time-dependent fluid flow

Abstract: A theoretical method is given for the determination of the shape of a fluid drop in steady and unsteady flows by making an expansion in terms of the drop deformation. Effects of fluid viscosity and interfacial tension are taken into account. Examples given include the determination of the shape of a drop in shear and in hyperbolic flow when each is started impulsively from rest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
292
1
1

Year Published

1986
1986
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 500 publications
(315 citation statements)
references
References 6 publications
14
292
1
1
Order By: Relevance
“…was also shown that the existence of a waist in the initial shape always led to breakup. Nearly spherical drops of arbitrary viscosity ratio were studied via domain perturbation techniques by Cox (1969} andRallison (1980}, and shown to attain steady shapes in an oscillatory manner in flows with vorticity. Finally, Rallison & Acrivos (1978) and Rallison (1981) have used the boundary-integral method to investigate some aspects of the time evolution of the drop shape and observed that the critical shear rate and mode of drop burst depended on the history of the flow.…”
Section: Introductionmentioning
confidence: 99%
“…was also shown that the existence of a waist in the initial shape always led to breakup. Nearly spherical drops of arbitrary viscosity ratio were studied via domain perturbation techniques by Cox (1969} andRallison (1980}, and shown to attain steady shapes in an oscillatory manner in flows with vorticity. Finally, Rallison & Acrivos (1978) and Rallison (1981) have used the boundary-integral method to investigate some aspects of the time evolution of the drop shape and observed that the critical shear rate and mode of drop burst depended on the history of the flow.…”
Section: Introductionmentioning
confidence: 99%
“…The droplet does not deform easily for K > 4. Cox 21) predicted the steady-state shape of the droplet and derived the following expression for the predicted ellipsoid. The time change in droplet shape under shear flow was observed for the PDMS82/PIB95 system at 23°C.…”
Section: Steady Shear Flow Methodsmentioning
confidence: 99%
“…The forces and deformation of dispersed droplets in flow fields have been studied for a long time, especially for the Newtonian droplets in Newtonian continuous phase, various models have been developed to predict the complex break-up behavior of droplets as well as coalescence [29][30][31][32][33]. The better understanding of dispersion mechanism has an important role in petroleum production and operation.…”
Section: Mechanistic Modelmentioning
confidence: 99%